FEATURES OF SOCIAL AND BIOLOGICAL HISTORY OF CHILDREN DURING THE FORMATION OF LTBI AND ITS PROGRESSION TO ACTIVE TUBERCULOSIS - Adzhablaeva D.N; Parpieva N.N (Western European Studies, 2024)
According to the WHO, a quarter of the world's population are carriers of latent tuberculosis and the risk of progression of latent tuberculosis to an active form throughout a person’s life is in the range of 5-15%. It is well known that children living in foci of tuberculosis infection are more at risk of infection and tuberculosis. It is important to establish the prognostic significance of risk factors that must be taken into account when planning further treatment measures for this cohort of the population. Purpose of the study: conduct analysis social risk factors and characteristics of the antenatal and intranatal periods of children’s development during the development of latent tuberculosis infection and its progression to active tuberculosis.
Keywords: tuberculosis; development; progression